The Importance of Thinking about Thinking - Ellie Collier (In the Library with the Lead Pipe, 2010)
A review of How We Decide by Jonah Lehrer I play Magic. It’s a fairly complicated card game which calls on many of the same skills needed for games like chess or poker. Poker has suits, Magic has colors. And I hate playing black. Unlike other colors, when I play a black card I often have to [...]